El informe sobre erosión de bases imponibles y traslación de beneficios de la OCDE: origen e implementación en un marco internacional y globalizado - Serrano Antón, Fernando (2014)
This work is intended to analyze circumstances leading to OCDE’s report on tax bases erosion and shifting benefits. Inconsistency of tax systems and unilateralism in current economic globalization framework might have led to asymmetric tax situations, mostly exploited by multinational companies. Means and tools used and proposed by several international institutions in order to implement legally binding actions through soft law and acceptance by different countries as method used in the fight against tax avoidance and fraud are also discussed.